The Hunchback of Notre Dame - Hugo, Victor (First Avenue Classics Ser., 2014)
Quasimodo, the hunchbacked bell-ringer of Notre Dame, faces insults and ridicule for his disturbing appearance. His adoptive father, Archdeacon Claude Frollo, is obsessed with the beautiful gypsy Esmeralda and orders Quasimodo to kidnap her. But when Quasimodo is caught and punished, Esmeralda takes pity on him. From that moment on, Quasimodo finds himself caught between love for the kind beauty and loyalty to man who raised him. A novel that challenges the value of appearances and social classes, this gothic romance by Victor Hugo was published in France in 1831. This is an unabridged version taken from the Isabel F. Hapgood translation of 1888.